2015
DOI: 10.5897/ijbc2015.0858
|View full text |Cite
|
Sign up to set email alerts
|

Population structure of small mammals with different seasons and habitats in Arditsy Forest, Awi Zone, Ethiopia

Abstract: A study on the population structure of small mammals was carried out in Aridtsy Forest, Awi Zone from August 2011 to February 2012 incorporating both wet and dry seasons. Sherman live traps and snap traps in four randomly selected different trapping grids where distinct habitat types, namely, natural forest, bushland, grassland and farmland were employed. During this study a total of 468 individuals, including eight species of small mammals (live traps) and 89 individuals counting six species of small mammals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 25 publications
1
1
0
Order By: Relevance
“…We also found that the number of females was more abundant than the males in most species captured. This study was in line with [23] which reported the high number of females during the wet season. This is due to the reproductive rates being higher during the rainy season in both sexes of small mammals as it is related to the polygyny behaviour in small mammals [24].…”
Section: Species Composition and Abundancesupporting
confidence: 92%
See 1 more Smart Citation
“…We also found that the number of females was more abundant than the males in most species captured. This study was in line with [23] which reported the high number of females during the wet season. This is due to the reproductive rates being higher during the rainy season in both sexes of small mammals as it is related to the polygyny behaviour in small mammals [24].…”
Section: Species Composition and Abundancesupporting
confidence: 92%
“…The sex ratio is likely biased towards females since females are more likely to travel farther than males do, increasing their risk of getting trapped. This leads to seasonal reproduction which causes newborn recruitment to peak near the end of the breeding season and results in a surge in the number of juveniles [23]. A study by [25] reported that the neuroendocrine mechanisms affect how birds and mammals regulate their seasonal reproductive cycles.…”
Section: Species Composition and Abundancementioning
confidence: 99%